Monetary Policy Transmission and Policy Coordination in China - Das, Sonali (IMF Working Papers; Working Paper, 2022)
We study the transmission of conventional monetary policy in China, focusing on the interaction between monetary and fiscal policy given the unique institutional set-up for macroeconomic policy making. Our results suggest some progress but also continued difficulties in the transmission of monetary policy. Similar to recent studies, we find evidence of monetary policy pass-through to interest rates. However, the impact of monetary policy measures that are not coordinated with fiscal policy is significantly weaker than that of coordinated measures. This suggests the need for further improvements to the interest-rate based framework.